1987
DOI: 10.1002/macp.1987.021880913
|View full text |Cite
|
Sign up to set email alerts
|

Ein Modell zur Beschreibung reversibler Copolymerisationen

Abstract: The reversible copolymerization is described by a model derived from simple kinetic assumptions. The copolymerization behaviour of a system can be calculated from 3 experimental parameters: composition of the monomer mixture, composition and diade distribution of the copolymer. Four additional model constants represent the connection with the thermodynamics of reversible copolymerization. The model leads to the same results as the Monte-Carlo method described in the literature. The temperature dependence of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…These new equations reduce to the expressions for the same quantities derived by Krüger et al [3] and used by Palmer et al [9] and Badeen and Dubé [10] when only terminal kinetics are considered (s 1 ¼ s 2 ¼ 1). They can be used along with Equation (6), (7), and (12) to solve for polymer composition and k p,copo for a copolymerization system with depropagation and penultimate unit effects.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…These new equations reduce to the expressions for the same quantities derived by Krüger et al [3] and used by Palmer et al [9] and Badeen and Dubé [10] when only terminal kinetics are considered (s 1 ¼ s 2 ¼ 1). They can be used along with Equation (6), (7), and (12) to solve for polymer composition and k p,copo for a copolymerization system with depropagation and penultimate unit effects.…”
mentioning
confidence: 87%
“…Lowry Case 1, which assumes that depropagation is only important when a depropagating monomer is attached to the same monomer type, i.e., depropagation by diad end groups, becomes a special case of Wittmer's model when only one of the homopropagation reactions is reversible. Krüger et al [3] modified the solution approach to Wittmer's model by defining the propagation probabilities. More recently, Kukulj and Davis [4] have derived an expression for average propagation rate coefficient (k p,copo ) by using terminal kinetics and the Lowry Case 1 model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowry Case I is a special case of Wittmer's model when only the homopropagation of monomer type 2 is reversible (k dp 11 k dp 12 k dp 21 0). Krüger et al [38] introduced a slightly modified approach compared to Wittmer's model by defining propagation probabilities, as recently updated by Badeen and Dubé [39]. An experimental study examining the influence of BMA depropagation on ST/BMA copolymer composition found that the Lowry Case I description of depropagation is applicable, i.e., BMA only depropagates when BMA is also present as the penultimate unit of the polymer chain [40].…”
Section: Copolymerizationmentioning
confidence: 97%
“…Because of this mathematical difficulty, it was until 1987 that the first systematic treatment of first-order terminal models with depropagation was given by Kruger et.al. [14]. Kruger's approach was based on the key assumption that the copolymer sequence can be described as a first-order Markov chain (Eq.…”
Section: Introductionmentioning
confidence: 99%